Global Observer for Homogegeous Vector Fields - Hammami, M. A. (Nonlinear Analysis: Modelling and Control, 2005)
This paper presents an algebraic approach to the problem of nonlinear observer design. We show, that an observer which converges globally and asymptotically can be designed for a class of homogeneous systems of odd degree.
Keywords: Homogeneous systems; Lyapunov function; asymptotic observer